Desarrollo de un módulo prototipo de sistema de generación hidroeléctrica basado en vórtice gravitacional - Ramón Campoverde, Jaime Daniel (2018)
Abstract:It is presented the development of a hydraulic prototype for the generation of electrical energy, based on the principle of gravitational vortex, this hydroelectric micro-system represents a feasible means of generation in isolated villages, where, the transport of electrical energy requires a high cost, due to the great distances. Its operation is based on the tangential entry of water to a circular tank, or spiral, which gives rise to the formation of a hydraulic vortex, whose rotational movement is used for the generation of electrical energy. The development of the prototype was based on the minimization of energy losses in the system, by optimizing aspects such as: tank geometry, inlet width, flow depth and discharge cone. The design, construction and validation of the prototype were guaranteed by a dimensional analysis process, whose objective was to extrapolate the results obtained to a constructive context of greater scale. The results of the hydraulic tests and the numerical modeling indicate that, with the geometry proposed in this research, the efficiency of the system is higher than 45%.